Inhibiting Corrosion of Biomedical-Grade Ti-6Al-4V Alloys with Graphene Nanocoating. (March 2020) - Malhotra, R.; Han, Y.M.; Morin, J.L.P.; Luong-Van, E.K.; Chew, R.J.J.; Castro Neto, A.H.; Nijhuis, C.A.; Rosa, V.
The identification of metal ions and particles in the vicinity of failed implants has raised the concern that biomedical titanium alloys undergo corrosion in healthy and infected tissues. Various surface modifications and coatings have been investigated to prevent the deterioration and biocorrosion of titanium alloys but so far with limited success. Graphene is a cytocompatible atom-thick film made of carbon atoms. It has a very high surface area and can be deposited onto metal objects with complex shapes. As the carbon lattice has a very small pore size, graphene has promising impermeability capacity. Here, we show that graphene coating can effectively protect Ti-6Al-4V from corrosion. Graphene nanocoatings were produced on Ti-6Al-4V grade 5 and 23 discs and subjected to corrosive challenge (0.5M NaCl supplemented with 2-ppm fluoride, pH of 2.0) up to 30 d. The linear polarization resistance curves and electrochemical impedance spectroscopy analysis showed that the graphene-coated samples presented higher corrosion resistance and electrochemical stability at all time points. Moreover, the corrosion rate of the graphene-coated samples was very low and stable ( 0.001 mm/y), whereas that of the uncoated controls increased up to 16 and 5 times for grade 5 and 23 ( 0.091 mm/y) at the end point, respectively. The surface oxidation, degradation (e.g., crevice defects), and leaching of Ti, Al, and V ions observed in the uncoated controls were prevented by the graphene nanocoating. The Raman mappings confirmed that the graphene nanocoating presented high structural stability and resistance to mechanical stresses and chemical degradation, keeping >99% of coverage after corrosion challenge. Our findings open the avenues for the use of graphene as anticorrosion coatings for metal biomedical alloys and implantable devices.